MICROBIAL CONTAMINATION TEST USING THE MOST PROBABLE NUMBER (MPN) METHOD ON SWEET SOY SAUCE AROUND UPN “VETERAN” JAKARTA PONDOK LABU CAMPUS MICROBIAL CONTAMINATION TEST USING THE MOST PROBABLE NUMBER (MPN) METHOD ON SWEET SOY SAUCE AROUND UPN “VETERAN” JAKARTA PONDOK LABU CAMPUS - Ariska Deffy Anggarany; Alisha Dian Prasasti; Amara Ayu Karlina; Anisa Puja Ningrum; Aurelie Reginia Iteh; Bimo Asrul Seno; Nabilah Siti Zahara (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2024)
Sweet soy sauce is a fermented soybean product widely used as a traditional Indonesian seasoning. Its production process involves specific microorganisms to develop unique taste, aroma, and texture characteristics. However, poor hygiene and sanitation can lead to microbial contamination, such as Coliform, which may degrade quality and pose health risks. This study aimed to evaluate the microbiological quality of sweet soy sauce using the Most Probable Number (MPN) method. Samples were collected from food vendors around the UPN "Veteran" Jakarta campus and tested using liquid media to detect the presence of Coliform. The results showed that sample 1 (street vendor) had an MPN value of 14 MPN/gram, exceeding the BPOM safety limit (3 MPN/gram), while sample 2 (packaged soy sauce from a minimarket) was within the safety limit at 3 MPN/gram. A confirmatory test detected the presence of Escherichia coli in sample 1 but not in sample 2. Proper product handling, implementation of Good Manufacturing Practices (GMP), and regular microbiological monitoring are necessary to ensure the safety of sweet soy sauce products.